Cross-sectoral learnings on emerging gender and social norms measures - CGIAR Gender Equality Initiative (CGIAR Initiative on Gender Equality, 2023)
As part of the Harnessing Gender and Social Equality for Resilience in Agrifood Systems (HER+) Initiative under the One CGIAR, scientists from the International Food Policy Research Institute, International Institute of Tropical Agriculture and FHI 360 are collaborating on the development of a Multidimensional Social Norms in Agrifood systems index. This index was recently featured in a webinar focusing on recently developed quantitative measures of gender and social norms that was organized by the Social Norms Learning Collaboratives and the Evidence-Based Measures of Empowerment for Research on Gender Equality (EMERGE) project. The discussion facilitated by Sushmita Mukherjee, Director of Gender and Adolescent Girls with Project Concern International in India featured experts from across 5 countries and 4 sectors who shared how they developed and tested measures of gender and social norms and what lessons they learned from their measurement experiences.